Respostas

2014-08-05T16:17:00-03:00
(H) x + 8 = 54
x = 54 - 8 
x = 46

(I) 7x - 2 - 5x = 18
7x - 5x = 18 + 2
2x = 20
x = 20 / 2
x = 10

(J) -x - 2x - 4 = 11
-3x = 11 + 4
-3x = 15
x = 15 / -3
x = -5

(K) 4 (x + 1) = 12
4x + 4 = 12
4x = 12 - 4
4x = 8
x = 8 / 4
x = 2
 



2014-08-05T16:17:20-03:00
H) x = 54 - 8
    x = 46
I) 7x - 5x = 18 + 2
   2x = 20
   x =  \frac{20}{2}
   x = 10
J) -x - 2x = 11 + 4
   -3x = 15 (-1)
   3x = -15
   x =  \frac{-15}{3}
   x = -5
K) 4x + 4 = 12
    4x = 12 - 4
    4x = 8
    x =  \frac{8}{4}
    x = 2